Effects of Exercise Training on Muscle and Functional Outcomes in Adults with Liver Cirrhosis: A Systematic Review - Priscila Meireles Calil Fontana; Rafael dos Santos Souza; Manuella Franco Cerqueira da Silva; Anete da Costa Medeiros; Yamana Dias de Matos; Laisa Liane Paineiras-Domingos (SN Comprehensive Clinical Medicine, 2026)
Abstract Objective To evaluate the efficacy and safety of physical exercise on muscle mass, strength, and functional capacity in adult patients with pre-transplant liver cirrhosis. Methods This systematic review (PROSPERO: CRD420261279439) followed PRISMA guidelines. We searched six databases (PubMed, EMBASE, Cochrane, VHL, Scopus, SciELO) for randomized controlled trials (RCTs) evaluating exercise in cirrhotic patients. Risk of bias and certainty of evidence were assessed using RoB 2 and GRADE, respectively. Results Four RCTs were included (135 analyzed patients). Supervised exercise significantly improved functional capacity (6-minute walk test distance up to + 69 m; cardiopulmonary effort time + 2.0 min) and muscle strength (isokinetic knee torque + 11 N.m; handgrip + 2.6 kgf) compared to usual care. Localized imaging (MRI/DXA) showed modest muscle mass gains, whereas total lean mass via bioelectrical impedance remained unchanged. Unsupervised home-based training yielded non-significant improvements. Zero exercise-induced variceal bleeding, acute decompensations, or severe adverse events occurred. Overall risk of bias raised “Some concerns” due to unblinded performance tests. Certainty of evidence (GRADE) was Moderate for functional capacity and muscle mass, and Low for muscle strength. Conclusion Structured, supervised physical exercise is a safe and effective intervention to improve functional capacity and muscle strength in stable liver cirrhosis. Supervision is crucial to achieve the stimulus threshold required to reverse sarcopenia. Further large-scale RCTs are needed to assess long-term pre-transplant outcomes.